The realistic reflection of adolescent outlook in Bhabendra Nath Saikia’s Antareep : Study - K. Dhanalakshmi,; Rao, Dr. A. Madhusudhana (International Journal of Psychosocial Rehabilitation, 2019)
Creative writing is a dignified expression of human life and the world. It reflects the thought process of a writer and mindsets of the different classes of society. From birth to the old age, there are many different stages of human life cycle. Among them the childhood can be called as the primary stage and the adolescence as the secondary stage. The age span ranging from birth to the puberty is known as the childhood period and the next period from puberty to legal adulthood is known as the adolescence period. Adolescence plays an important role in the development of human life. In this period the behaviors and cognitive styles of an individual undergo many changes. Therefore the adolescence period has been analyzed by the psychologists in a distinctive method of analysis. Similarly in the field of creative writing, different writers have portrayed the outlook of the adolescence period through their writings. In Assamese literature besides writings for children and teenagers, the reflection of the adolescent outlook is vividly apparent in other literary genres as well. The realistic reflection of adolescent outlook in the literary works of ‘Bhabendra Nath Saikia’ provides a clear evidence of this aspect. Therefore we see that although psychology and literature are two different fields of study, the interrelation between these two autonomous subjects necessitates an interdisciplinary analysis.